"Programa Educa Pontal": gestão de processos formativos no contexto do Pontal do Paranapanema - MAGRO, Enio (2022)
This master's research was developed in Line 01: Public Policies in Education, training processes and diversity, of the Graduate Program in Education at “Universidade do OestePaulista (UNOESTE)”. The genesis of the research took place from training processes carried out in an extension program called "ProgramaEducaPontal", a partnership between the Pro-Rectory of Extension and Community Action of UNOESTE and the Regional Board of Education of Mirante do Paranapanema/SP. The program is directly aligned with the programs of the São Paulo State Department of Education: InovaEducação and the Program for the Improvement of Coexistence and School Protection –, in addition to the Sustainable Development Goals and the National Common Curricular Base, developed in the contexts of the State's education directorates to promote a quality curriculum and comprehensive training of students. Through an Extension Management System, manages the records of extensive actions linked to the Program and data on themes, objectives, participants, methodology and results are inserted into this system. Therefore, the following research questions emerged: What are the managerial and documentary data of the EducaPontal Program? How do these data allow an analysis of the training processes carried out in the context of Pontal do Paranapanema? To answer these questions, the general objective was: To identify and analyze the managerial and documentary data of the EducaPontal Program. The research had a qualitative-quantitative approach, of the descriptive type. In order to characterize the context of the Education Board of Mirante do Paranapanema, documental sources present in the administrative panel of the Regional Education Director were identified, selected and analyzed. For the theoretical foundation of the research, the Scielo and Brazilian Digital Library of Theses and Dissertations databases were consulted, whose publications similar to the theme of this research were problematized, in addition to consulting authors who discuss university extension, training processes and social inclusion. To identify and analyze the managerial and documentary data of the EducaPontal Program, a report from the UNOESTE Extension Management System was used. Descriptive statistics was used to analyze the data. It was possible to characterize the management data of the EducaPontal Program and the training processes offered to teachers and students belonging to the Regional Board of Education of Mirante do Paranapanema. Different training workshops were carried out with a workload between 04 and 80 hours, an average of 100 to more than 1,000 participants, these being basic education teachers, managers and high school students and topics such as citizenship, ethics, teaching and learning, training of skills and others.